Retratos da arte e do artista: projeto autobiográfico de José Saramago - Marcon, Adriana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation proposes an analysis of Manual of Painting and Calligraphy (1977) and Memories of my Youth (2006), written by the Portuguese writer José Saramago, seeking to highlight their singularities, similarities and differences. It objectifies to show how the novel Manual of Painting and Calligraphy, for having autobiographical vestiges, is the sign of the portrayal of the art/ writing that will be put into practice in Saramago’s future writing, while Memories of my Youth, his autobiography, shows the portrayal of the artist/writer when his was young. With the choice of these books that represent, respectively, the beginning and the end of an autobiographical and literary project, it intends to consider the genre tensions installed in the autobiography when written by a novelist, as well as the presence of autobiographical vestiges in a novel. To reach this objective, it appeals to a theoreticalmethodological contribution based on specialists of Saramago’s writing, on reflections about novel and autobiography, and on studies of the structural analysis of narrative. After a long way of detailed reflections about the objects of this dissertation, it accomplishes the comparison between the narratives, evidencing the possible connections and differences between both texts

Esta dissertação propõe uma análise de Manual de Pintura e Caligrafia (1977) e As Pequenas Memórias (2006), do escritor português José Saramago, procurando destacar suas singularidades, semelhanças e diferenças. Objetiva-se mostrar como o romance Manual de Pintura e Caligrafia, por possuir laivos autobiográficos, é prenúncio do retrato da arte/escrita exercida por Saramago na sua produção literária vindoura, enquanto As Pequenas Memórias, sua autobiografia propriamente dita, exibe o retrato do artista/escritor nos tempos juvenis. Com a escolha dessas obras que representam, respectivamente, o ponto inaugural e o porto de chegada de um projeto autobiográfico que é também literário, pretende-se evidenciar as tensões de gêneros instaladas na autobiografia quando produzida por um ficcionista, bem como a presença de indícios autobiográficos na elaboração de um romance. Para cumprir este propósito, recorreu-se a um aporte teórico-metodológico pautado na fortuna crítica saramaguiana, na reflexão sobre os gêneros romanesco e autobiográfico e nos estudos de análise estrutural da narrativa. Após um caminho minucioso de reflexões acerca dos objetos que presidem a dissertação, efetua-se a comparação entre as narrativas estudadas, evidenciando-se os pontos de semelhança e de contraste entre ambas
Keywords: Saramago, José, 1922-2010; Literatura portuguesa; Ficção portuguesa; Autobiografia; Portuguese literature